2009
DOI: 10.3201/eid1509.080759
|View full text |Cite
|
Sign up to set email alerts
|

Recent Ancestry of Kyasanur Forest Disease Virus

Abstract: Clinicians in Asia should consider this disease when diagnosing acute febrile illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 21 publications
2
82
2
2
Order By: Relevance
“…Both found that the three genome segments undergo roughly 10 À4 changes per nucleotide per year, or about two base changes per year for the entire genome. Carroll et al observed that the rate of evolution of CCHFV was somewhat slower than that reported for the mosquito-borne bunyavirus, Rift Valley fever virus and the tick-borne flavivirus, Kyasanur Forest disease virus (Bird et al, 2008;Mehla et al, 2009), but the differences were modest. Because the evolutionary rate of a virus is simply a way of measuring its genetic diversity, both groups reported that the CCHFV M segment was evolving more rapidly than the S or L segment.…”
Section: Genetic Driftmentioning
confidence: 75%
“…Both found that the three genome segments undergo roughly 10 À4 changes per nucleotide per year, or about two base changes per year for the entire genome. Carroll et al observed that the rate of evolution of CCHFV was somewhat slower than that reported for the mosquito-borne bunyavirus, Rift Valley fever virus and the tick-borne flavivirus, Kyasanur Forest disease virus (Bird et al, 2008;Mehla et al, 2009), but the differences were modest. Because the evolutionary rate of a virus is simply a way of measuring its genetic diversity, both groups reported that the CCHFV M segment was evolving more rapidly than the S or L segment.…”
Section: Genetic Driftmentioning
confidence: 75%
“…Dolaşımdaki AHFV suşları arasın-daki rekombinasyona bağlı olarak, nükleotid sayılarında kü-çük farklılıklar gözlenebilmektedir (17 (23). Ancak suşun referans suşla da özdeş olması, sonradan bir laboratuvar kontaminasyonu olarak yorumlanmıştır (24).…”
Section: Etyolojiunclassified
“…İki virus arasındaki farklılaş-manın geçmişinin, önceleri 66-177 yıl olduğu, hatta 1942 yılı gibi yakın bir tarihe uzandığı hesaplanmışken (24,27); insan olgularının yanı sıra kenelerden izole edilen 16 AHFV suşu-nun ve arşivde tutulan üç KFDV suşunun tam genom dizileri çıkarılarak yapılan son filogenetik analizin bulguları, farklı-laşmanın 700 yıl (121-1487 yıl) kadar gerilere gidebileceğini göstermektedir. Bu bulgular, KFDV'nin, endemik olduğu böl-geden yaklaşık 4000 km uzakta olan Suudi Arabistan'a, çok yakın bir tarihte girmiş olamayacağını düşündürmektedir.…”
Section: Etyolojiunclassified
“…Since 1955, the disease has been known in the Southwest of India. After comparing 48 KFDV isolates, it was concluded that the isolates from India, Saudi Arabia (Alkhurma virus) and China shared their last common ancestor around 1942 (Mehla et al, 2009). However, it should be added that the authors questioned the authenticity of the Chinese isolate due to its complete identity with the Indian reference strain isolated in 1957.…”
Section: Kyasanur Forest Diseasementioning
confidence: 99%
“…The reason for this is the low viremia. In addition, it is considered possible that cattle play a role as amplification host (Mehla et al, 2009). The ratio of clinical and subclinical infections of >50 % is high (Pandit, 1960).…”
Section: Kyasanur Forest Diseasementioning
confidence: 99%